Individual entrepreneurship orientation, intention and entrepreneurial career choice among UNIKL HTVET students - Ainul Yusnita, Mohamad Yusop (2020)
The main purpose of this study is to determine the relationship of individual entrepreneurial orientation and intention among Universiti Kuala Lumpur (UniKL) Higher Technical Vocational Education and Training (HTVET) students towards their entrepreneurial career preferences. Specifically, it aims at investigating the mediating effect of entrepreneurial intention on the relationship between individual entrepreneurial orientation and entrepreneurial career choice. The motivation for this study is driven by the lack of findings in the literature concerning the relationships between entrepreneurial orientation and intention of HTVET students, which are believed to influence one to choose the entrepreneurial career path. Due to this reason, the researcher intends to investigate the relationships amongst the variables that may better explain such relationships specifically concerning the HTVET students. Accordingly, this study uses the Social Cognitive Theory to map and position the possible relationships between the variables in the conceptual framework. The study utilizes a self-administered questionnaire, which was randomly distributed to 440 Bachelor of Engineering Technology students at Universiti Kuala Lumpur (UniKL). 265 questionnaires were returned and usable for analysis. The Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to analyse the relationship between the related variables in the study. The results reveal that individual entrepreneurial orientation and entrepreneurial intention have a significant positive impact on the entrepreneurial career choice of UniKL HTVET students. The findings further show that entrepreneurial intention mediates through individual entrepreneurial orientation on the entrepreneurial career choice of UniKL HTVET students. Finally, managerial, policy and theoretical implications, as well as directions for future research, are also highlighted.